2015
DOI: 10.1039/c4gc02522a
|View full text |Cite
|
Sign up to set email alerts
|

A novel green protocol for ligand free Suzuki–Miyaura cross-coupling reactions in WEB at room temperature

Abstract: A highly efficient green protocol for palladium acetate-catalysed ligand-free Suzuki–Miyaura cross-coupling reactions in neat ‘water extract of banana (WEB)’ was developed. Suzuki–Miyaura reaction proceeds in WEB at very short reaction times under ‘ligand/external base/external promoters/organic medium’ free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(56 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…Green procedure of coupling reaction is booming, and a lot of ligand‐free or green solvent coupling reactions are rapidly developing. Recently, some chemists such as Basu, Liu, Bora, Liu, Schatz, Sarma, Handa (Scheme B) reported a series of ligand‐free Suzuki–Miyaura coupling reaction to yield the biaryl products. Since the first research reported by Genêt group in 1997, potassium aryltrifluoroborates were widely used as an alternative to organoboronic acid in Suzuki–Miyaura coupling reaction recently .…”
Section: Introductionmentioning
confidence: 99%
“…Green procedure of coupling reaction is booming, and a lot of ligand‐free or green solvent coupling reactions are rapidly developing. Recently, some chemists such as Basu, Liu, Bora, Liu, Schatz, Sarma, Handa (Scheme B) reported a series of ligand‐free Suzuki–Miyaura coupling reaction to yield the biaryl products. Since the first research reported by Genêt group in 1997, potassium aryltrifluoroborates were widely used as an alternative to organoboronic acid in Suzuki–Miyaura coupling reaction recently .…”
Section: Introductionmentioning
confidence: 99%
“…Although recently some efficient methodologies have been developed for SMC by avoiding external base and ligands, there is still a demand to develop new synthetic protocols since unexpected results can be seen in SMC by a small change of reaction conditions like temperature, ligand, base, nature of substrates, solvent, etc . Typical trends in substrate selectivity and reactivity may be broken .…”
Section: Introductionmentioning
confidence: 99%
“…Various Pd‐catalyzed reactions viz. Suzuki‐Miyaura and Sonogashira coupling, popular name reactions (for example Dakin and Henry reaction) and other organic synthesis such as peptide synthesis, azidation of aromatics and synthesis of 3‐carboxycoumarins have been successfully performed in this green reaction medium. Although WEB can be used alone, in some cases it has been mixed with organic solvents like ethanol and iso ‐propanol to increase the miscibility of reagents and starting materials so that the reactions furnish higher yields of the products .…”
Section: Introductionmentioning
confidence: 99%